Exploration Of Village Government Taxpayer Compliance - Febriyanto, Moh.; Faisol, Moh. (Journal of Multiperspectives on Accounting Literature, 2023)
Purpose: The Aims of this reseach to explore the tax compliance of HDD Village government using a qualitative approach. Methodology/approach: Researchers used the case study method and conducted in-depth interviews with three informants about HDD village tax compliance and perfected it by observing and documenting. The research data is then analyzed by starting the process of data reduction, data presentation, and conclusions and ending with data validity testing using trianguation of methods and sources. Findings: The results of this study show that tax compliance carried out by HDD Village to comply with the fulfillment of obligations to have an NPWP, tax collection/withholding, tax payment, and tax reporting has been carried out properly. However, specifically for the 2020 and 2021 tax years, it has not been optimal, due to the Covid-19 pandemic which focuses on using the budget for Covid-19 mitigation so that the village government has not collected/withheld/collected taxes on taxes owed. Practical implications: The implication of this research is that the ignorance of village officials on tax obligations is one indication of fulfilling tax compliance. Therefore, it is important for the directorate general of taxes intensely to socialize and assist village officials in fulfilling tax obligations and will automatically improve tax compliance. Originality/value: The research results show that the tax collection and withholding process that has been carried out by HDD Village, the tax burden withheld by HDD Village and should be paid by the goods/services provider (Shop or Service Provider) is fully borne by HDD Village.